(untitled) (Research, Society and Development, 2021)
This article analyzes the representation of women accused of introducing false banknotes in the press in Rio de Janeiro during the First Republic (1889-1930). For this purpose, he will use the case of Quitéria de Jesus as an example due to its wide public repercussion and its result in 1909. As the main source, crime stories taken from some periodicals are used and are intersected with other complementary sources, such as the report of the Minister of Justice and Interior Affairs of 1909. Through them, we will try to show how the coverage of the case raised gender conceptions that impacted their criminal sentence and marked the way in which these criminals were portrayed in the journalistic milieu.